Le(s) pont(s) de Crimée avant 2014. Les discontinuités d’une longue histoire - Denis Eckert; Ivan Savchuk (M@ppemonde)
Numerous projects for bridges across the Kerch Strait were conceived in the past, prior to the current bridge commissioned in 2018. The focus is on the decisions that successively led successive protagonists in this history to launch (or abandon) projects between 1903 and 2014, and the factors of economic geography and geopolitics that guided these decisions over time. In conclusion, one can imagine what effect a normalization of Crimea’s international legal status might have on today’s bridge traffic.